Inflammation: A Network in the Pathogenesis of Status Epilepticus - Wang, Ming; Chen, Yinghui (Frontiers in Molecular Neuroscience, 2018)
Status epilepticus (SE) is an abnormally prolonged or recurrent epileptic seizure that is a serious, life-threatening medical emergency. Notably, it requires prompt, aggressive treatment. SE is characterized by high mortality and morbidity. However, its pathogenesis remains unclear. Numerous studies of SE have reported widespread brain inflammation, suggesting that inflammation plays a vital role in the occurrence and development of SE. This article reviews current knowledge regarding the role of inflammation in SE.